Combination drug therapy against OAB normalizes micturition parameters and increases the release of nitric oxide during chemically induced cystitis. Issue 1 (7th February 2020) - Patel, Bhavik; Perez, Fernando; Aronsson, Patrik; Alothmani, Ranya; Carlsson, Thomas; Winder, Michael
Abstract: Today, monotherapy is the most common pharmacological treatment option for patients suffering from overactive bladder (OAB). Recent reports have indicated potential benefits of combination therapy, using a muscarinic antagonist and a β3 ‐adrenoceptor agonist. This may be of particular interest for therapy‐resistant patients with OAB and concomitant cystitis. The objective of the current study was to assess how combination therapy affects bladder parameters in health and cystitis and if the efficacy of the drugs can be linked to altered release of nitric oxide (NO). Rats were pretreated with either a combination of the muscarinic antagonist tolterodine and β3 ‐selective adrenoceptor agonist mirabegron or saline for 10 days. Forty‐eight hours prior to assessing micturition parameters in a metabolic cage, the rats were intraperitoneally injected with cyclophosphamide, causing cystitis, or saline. Urine samples were collected and analyzed for NO content. Bladder contractile properties were assessed in an organ bath setup. Induction of cystitis led to bladder overactivity. Combination therapy normalized bladder parameters. Both induction of cystitis and drug treatment increased the release of NO. The innate contractile properties of the bladder were unaffected by combination therapy. This study demonstrates positive effects of combination drug therapy on symptoms of OAB, possibly indicating it to be a good option for treatment of OAB during concomitant cystitis. It remains to be determined if increased release of NO is crucial for successful pharmacological treatment of bladder overactivity during cystitis.